From peptides to DNA: All required steps can be catalyzed - Lei Shi; Mériem Senissar; Kirsten Leistner; Carsten Jers; Ivan Mijakovic (Proceedings of the National Academy of Sciences, 2026)
Ensuring information flow (heredity) and metabolic processes (catalysis) are two important prerequisites for early evolution. The widely accepted “RNA world” theory proposes that ancient RNAs ensured both heredity and catalysis during the transition from prebiotic to biotic evolution. However, alternative hypothetical molecules and processes have also been proposed, suggesting that catalytic peptides may have existed before polynucleotides, and that their sequences were later reverse translated into genes. Our objective was to experimentally address these alternative theories by asking whether the steps required for the hypothetical conversion of peptide sequences into DNA could be catalyzed by the existing molecular kit. The reactions we tested comprise i) step-wise degradation of peptides by a processive amino peptidase, sequentially releasing amino acids, ii) matching the identity of released amino acids to codons by aptazymes (RNA adapters that recognize amino acids and self-cleave and release specific codon triplets in response), and iii) ligating codon triplets into longer RNAs that can be reverse-transcribed into DNA. In a hypothetical processive system based on these reactions, the resulting DNA sequence would match the sequence of amino acids in the starting peptide. Our results suggest that all these steps can be catalyzed, and therefore the possibility of reverse translation occurring at some point in early evolution should not be disregarded.